Pengembangan Media Pop Up Book dalam Meningkatkan Budaya Literasi Program Pojok Baca di SMP Negeri 1 Berastagi - May Rifany; Rina Devianty; Edi Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The research and development is titled “Development of Pop-Up Book Media in Enhancing Literacy Culture in the Reading Corner Program at SMP Negeri 1 Berastagi.”This development research aims to determine: (1) The design of pop-up book media; (2) The development of pop-up book media in enhancing student literacy; (3) The feasibility of pop-up book media in improving student literacy. This research is conducted using a Research and Development (R&D) model with the 4D model, which includes Define (definition), Design (design), Development (development), and Dissemination (dissemination). The subjects of this research are students of SMP Negeri 1 Berastagi, totaling 35 individuals. The instruments used in this research include questionnaires to assess the development, feasibility, and effectiveness of the media. Data analysis techniques include product data analysis, initial data analysis, and hypothesis testing.The results show that the pop-up book media received evaluations of 81% from media experts, 92% from material experts, and 65% from language experts. There was an average increase in student scores of 83%, indicating a significant change between pretest and posttest scores. The conclusion of the research is that the pop-up book media for drama content is suitable for use in literacy activities of the reading corner program. Recommendations for future research include being more meticulous in planning the development of pop-up book media, ensuring it aligns with the needs and characteristics of students.